AKTIVITAS ANTIJAMUR FRAKSI KAYU SECANG TERHADAP Candida albicans DAN BIOAUTOGRAFI: Indonesia - Senja, Salsadella Juwita; Indrayati, Ana; Harjanti, Reslely (Jurnal Buana Farma, 2025)
Sappan (Caesalpinia sappan L.) is a plant of the Caesalpiniaceae family that is used for traditional medicine. Utilized Secang (Caesalpinia sappan L.) is a plant from the Caesalpiniaceae family whose wood has long been used in traditional medicine and contains compounds such as brazilin, flavonoids, saponins, propane, tannins, and terpenoids with potential antifungal activity. Fungal infections, particularly Candida albicans, remain common health problems, and although antifungal drugs such as fluconazole are widely used, resistance cases continue to increase. This study aimed to evaluate the antifungal activity of secang wood extract and its fractions against C. albicans and to identify the most active compound group using thin-layer chromatography (TLC) bioautography. Secang wood was extracted by maceration with 96% ethanol and fractionated with n-hexane, ethyl acetate, and water, followed by antifungal testing using the paper disc diffusion method at concentrations of 6%, 9%, and 12%, with fluconazole as a positive control and 3% DMSO as a negative control. Data were analyzed using two-way ANOVA and showed normal distribution (Sig > 0.05). The results demonstrated that the extract, n-hexane fraction, ethyl acetate fraction, and water fraction inhibited the growth of C. albicans, with the water fraction at 12% producing the largest inhibition zone of 16.19 mm, categorized as strong activity. TLC bioautography of the water fraction revealed the presence of tannins as active compounds responsible for antifungal activity.